Simulation of the Potential Impacts of Projected Climate and Land Use Change on Runoff under CMIP6 Scenarios - Haider S.; Masood M.U.; Rashid M.; Alshehri F.; Pande C.B.; Katipo?lu O.M.; Costache R. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Assessing the impacts of climate change and land use/land cover changes on water resources within a catchment is essential because it helps us understand how these dynamic factors affect the quantity, quality, and availability of freshwater. This knowledge is crucial for making informed decisions about water management, conservation, and adaptation strategies, especially in regions facing increasing environmental uncertainties and challenges to water resource sustainability. In Pakistans Kunhar River Basin (KRB), this investigation explores the potential effects of shifting land use/land cover (LULC), and climate on stream flows. The SWAT (Soil and Water Assessment Tool), a semi-distributed hydrological model, and the most recent Coupled Model Intercomparison Project phase 6 (CMIP6) dataset from multiple global climate models (GCMs) were used to evaluate these effects. The temperature and precipitation data were downscaled using the CMhyd software